2022
DOI: 10.1016/j.heliyon.2021.e08622
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-derived exosomes and copper sulfide nanoparticles attenuate the progression of neurodegenerative disorders induced by cadmium in rats

Abstract: The goal of the current study was to investigate the therapeutic effects of exosomes derived from mesenchymal stem cells (MSCs-Exo) and copper sulfide nanoparticles (CuSNPs) as biomaterials in order to understand the mechanisms that contribute to overcoming cadmium (Cad) induced neurological disorders in rats. Animals were divided into five groups (n = 10): group 1 was served as a negative control and receive vehicle saline (Con), group 2 Positive control groups were received Cad as cadmium chloride at a dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Previous reports have demonstrated that the production of free radicals is, to some extent, associated with changes in AChE activity in the brain [54,55]. The findings of the current study showing the inhibition of AChE activity in the brain exerted by Cd and CN confirm the observations of previous studies suggesting that the inactivation of AChE enzymes is due to the occupation of its active sites by pollutants [56,57].…”
Section: Discussionsupporting
confidence: 90%
“…Previous reports have demonstrated that the production of free radicals is, to some extent, associated with changes in AChE activity in the brain [54,55]. The findings of the current study showing the inhibition of AChE activity in the brain exerted by Cd and CN confirm the observations of previous studies suggesting that the inactivation of AChE enzymes is due to the occupation of its active sites by pollutants [56,57].…”
Section: Discussionsupporting
confidence: 90%
“…In Zaazaa's proof‐of‐concept animal study, BM MSC‐derived sEVs were coupled with copper sulfide nanoparticles, acting as neuroprotective agents. [ 106 ] This system improved cholinergic function in the brain tissue of cadmium‐treated rats and reduced oxidative stress and inflammation by upregulating nerve growth factor and BDNF while downregulating TNF‐α & NF‐κB.…”
Section: Neurosurgery and Biomaterial‐assisted Sc‐sev Therapymentioning
confidence: 99%
“…Furthermore, Cd exposure may contribute to AD due to degenerative brain alterations [ 220 ]. In a recent study investigating the potential of NPs and exosomes to ameliorate neurological disorders, copper sulfide NPs and MSC-derived exosomes were co-delivered to rats in a Cd-induced neurological disorder model [ 221 ]. Improved anticholinesterase, antioxidant, and anti-inflammatory responses were observed after IV injection of MSC-derived exosomes and copper sulfide NPs.…”
Section: Biomedical Applications In Tissue Engineering and Neurodegen...mentioning
confidence: 99%
“…Improved anticholinesterase, antioxidant, and anti-inflammatory responses were observed after IV injection of MSC-derived exosomes and copper sulfide NPs. Histological evaluations revealed that treatment with MSC-derived exosomes and copper sulfide NPs decreased the toxic effects of Cd on brain tissue and reduced degenerative alterations originating from neuronal disorders [ 221 ]. Future investigations should evaluate the applications of exosomal-membrane-coated NPs in the delivery of biomaterials, drugs, and genes.…”
Section: Biomedical Applications In Tissue Engineering and Neurodegen...mentioning
confidence: 99%